Macromineral requirements for maintenance and growth in male and female hair sheep - Herbster, Caio J. L.; Abreu, Matheus L. C.; Brito Neto, Antonio S.; Mendes, Marcilio S.; Silva, Luciano P. da; Marcondes, Marcos I.; Mazza, Pedro H. S.; Cabral, Luciano S.; Bezerra, Leilson R.; Oliveira, Ronaldo L.; Pereira, Elzania S. (Frontiers in Veterinary Science, 2023)
We estimated the net requirements for Ca, P, K, Mg, and Na for gain (NCag, NPg, NKg, NMgg, and NNag) and maintenance (NCam, NPm, NKm, NMgm, and NNam) in male and female hair sheep. Six datasets with 248 individual records of hair sheep (139 non-castrated males, 75 castrated males and 34 females) were used to estimate the net macromineral requirements for gain. To estimate the net macromineral requirements for maintenance, 52 observations (26 non-castrated and 26 castrated males) were used. A meta-analytical approach was applied, using non-linear mixed effects models and the study as a random effect. Based on information criteria for model selection, heterogeneous variance functions were more likely to describe mineral requirements with a low level of model selection uncertainty. The adopted criteria allowed the choice of the best models to represent the macromineral requirements. The chosen models explained the observed variability in the sex, and the choices were based on a low level of uncertainty (w ⩾ 0.90). Irrespective of sex, NCag and NPg decreased with increasing BW from 10 to 30 kg and average daily gain (ADG) of 150 g/day, ranging from 1.71–1.38; 1.83–1.57; 1.82–1.51 of Ca and 0.86–0.66; 0.92–0.78; 0.92–0.75 of P for non-castrated males, castrated males, and females, respectively. The NKg remained constant, with mean values of 0.26 g/day. The NNag range was 0.17 to 0.14 g/day for non-castrated males, 0.20 to 0.25 g/day for females, and constant (0.18 g/day) for castrated males with an increase in BW from 10 to 30 kg and an ADG of 150 g/day. Macromineral requirements for maintenance (mg/kg BW) and retention (%) were 23.70 and 54.30 for Ca, 25.33 and 79.80 for P, 11.74 and 5.00 for K, 2.63 and 8.50 for Mg, and 7.01 and 8.10 for Na for males. The International Committees did not provide inferences about the sex influence on mineral requirements. Our study indicates that sex is one factor that influences the macromineral requirements for gain. The information generated in this study can be used to optimize the mineral management of hair sheep in the growing phase in tropical regions.